2013
DOI: 10.1073/pnas.1301951110
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of nucleoid structure regulated by mitochondrial fission contributes to cristae reformation and release of cytochrome c

Abstract: Mammalian cells typically contain thousands of copies of mitochondrial DNA assembled into hundreds of nucleoids. Here we analyzed the dynamic features of nucleoids in terms of mitochondrial membrane dynamics involving balanced fusion and fission. In mitochondrial fission GTPase dynamin-related protein (Drp1)-deficient cells, nucleoids were enlarged by their clustering within hyperfused mitochondria. In normal cells, mitochondrial fission often occurred adjacent to nucleoids, since localization of Mff and Drp1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
195
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(218 citation statements)
references
References 35 publications
22
195
0
Order By: Relevance
“…Recently, mitochondrial fusion and fission factors have been shown to influence the organization of mtDNA nucleoids. 41,52,53 In the present study, we found that Mic60/Mitofilin has an important role in the maintaining of mtDNA nucleoid organization and function in mammals ( Figures 5B and 6a). Thus, an important question is how Mic60/Mitofilin regulates the distribution and size of mtDNA nucleoids?…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Recently, mitochondrial fusion and fission factors have been shown to influence the organization of mtDNA nucleoids. 41,52,53 In the present study, we found that Mic60/Mitofilin has an important role in the maintaining of mtDNA nucleoid organization and function in mammals ( Figures 5B and 6a). Thus, an important question is how Mic60/Mitofilin regulates the distribution and size of mtDNA nucleoids?…”
Section: Discussionsupporting
confidence: 61%
“…Previous study showed that Mic60/Mitofilin was contained in purified HeLa mtDNA nucleoids 49 and embedded in mitochondrial inner membrane with its C-terminus facing mitochondrial intermembrane space. 47,50 We then checked the effect of A recent study found that the deletion of Drp1 results in enlarged and clustered mitochondrial nucleoids; 41 we showed that Mic60/Mitofilin deficiency caused a remarkable reduced Drp1 ( Figure 4D). To investigate whether the clustering of mtDNA nucleoids induced by shMic60 is due to downregulation of Drp1, we overexpressed Drp1-YFP in WT or shMic60 MEFs and analyzed the morphology of mitochondria and mtDNA nucleoids.…”
Section: Downregulation Of Mic60/mitofilin Causes Giant Mitochondria mentioning
confidence: 97%
See 1 more Smart Citation
“…22 Recently, Ban-Ishihara reported that Drp1-dependent mitochondrial fission regulates cytochrome c release via mitochondrial DNA distribution and cristae reformation. 23 Presumably, mitochondrial fragmentation is determined as a balance between fission and fusion of mitochondria. Although accumulation of fission GTPase Drp1 on mitochondria during apoptosis has been reported by several studies, 21,24-26 insufficient mitochondrial fusion might also contribute to cellular apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that in a rhabdomyosarcoma carrying 75 -80% of the MELAS A3243G mutations, knockdown of the profission proteins hDrp1 or human fission factor (hFis1) resulted in increased heteroplasmy levels of the mutant allele, which might be attributed to decreased mitophagic clearance of mutant mtDNA containing mitochondrial fragments [96], although this was not formally tested. Alternatively, inhibition of fission by dynamin-related protein-1 (Drp1) knockdown might result in a higher threshold of expression of an OXPHOS phenotype as it also seems to promote nucleoid clustering and thus perhaps functional complementation [96,97], Conditional knockouts of Mfn1 and 2 in mouse skeletal muscle result in the accumulation of mutations as well as severe mtDNA depletion in double knockout mice [87]. This seems counterintuitive considering that a more fragmented mitochondrial network might stimulate selective mitophagy and thus would help in selecting against mutant mtDNA molecules.…”
Section: (E) Putting the Theories To The Testmentioning
confidence: 99%